Food safety in hydroponic systems: crop growth and pathogen reduction with physical and biocontrol interventions - Moore, Markanna (My University, 2025)
Hydroponic cultivation has the potential to increase the sustainability of vegetable production through intensive production of crops, and more efficient resource use than soil-based cultivation. However, the recirculating nutrient solution that increases water use efficiency in hydroponic systems also risks the rapid spread of contaminants such as bacterial human pathogens which survive in moist or wet environments. This dissertation explores sustainable methods of hydroponic nutrient solution treatment, using UV-C irradiation or competition from beneficial bacteria, in order to mitigate food safety risks associated with hydroponic leafy green production. The first study investigated the survival of generic Escherichia coli in small-scale hydroponic systems growing romaine lettuce and assessed the efficacy of ultraviolet-C (UV-C) light treatment for decontamination. The UV treatments resulted in significant average reductions of E. coli in the nutrient solution. However, the E. coli population also declined naturally over the weeks following the inoculation, independent of the UV-C treatment. Survival of E. coli beyond one week is limited in the nutrient solution, when not considering its potential colonization of various surfaces within the hydroponic system. UV treatment has the potential to be used as a preventative safeguard on the microbial safety of the hydroponic production system. Having established the efficacy of UV treatment for the reduction of human pathogens in hydroponic systems, the next step was to examine the impact of the same UV treatment on plant growth in the absence of human pathogens. Nutrient solution samples were collected and analyzed for macronutrients N, P, and K before and after UV treatments, and no significant differences were found. Plant growth was assessed through measurements of height, chlorophyll fluorescence, and SPAD value, neither of which were found to differ significantly from control groups receiving no UV treatment. The research findings contribute to the potential use of UV light in hydroponic systems to have minimal impact on the plant growth of the crops grown in the systems.   While the UV treatment effectively reduced pathogens in the recirculating nutrient solution, random samples showed that bacterial counts were higher in samples of root tissue and growing media, indicating that bacterial colonies could survive on a variety of surfaces within the system despite the UV treatment. As a result, the next study explored an alternative treatment using a plant growth-promoting bacteria product containing Enterobacter cloacae, Citrobacter freundii, Pseudomonas putida, and Comamonas testosteroni as a biocontrol agent which was incorporated into the nutrient solution and circulated to reach all surfaces within a hydroponic system growing kale microgreens. Compared to UV treatments, there were no significant differences in the reduction of E. coli between the biocontrol and UV systems, though the UV system did significantly reduce E. coli compared to the controls. No significant differences were observed in plant height, fresh weight, or SPAD value. Overall, the results indicate that UV remains a more effective broad-spectrum microbial intervention for hydroponic nutrient solution, compared to the beneficial bacteria product evaluated here. The next study compares the effects of two commercially available plant growth-promoting bacteria (PGPB) products on the growth of hydroponic kale microgreens. Parameters measured include height, chlorophylls a and b, carotenoids, and ascorbic acid content. While the Pseudomonas putida-based PGPB product had a higher average height, chlorophyll a, and chlorophyll b, it was not significantly different from the Lactobacillus casei-based PGPB product or the control group. While the PGPB products investigated show potential for improved crop performance, further studies using additional products, bacterial strains, and hydroponic crops will be needed to better understand the broader impacts of PGPB on parameters of crop growth. These studies collectively demonstrate that UV-C water treatments are a safe and sustainable option to add a preventative food safety intervention to the cultivation of hydroponic leafy greens. No significant impacts on plant growth resulted from the interventions tested, but the UV water treatments did result in significant pathogen reduction. While PGPB has the potential to reach interior surfaces within hydroponic systems that remain inaccessible to UV water treatments, more research is required to evaluate and optimize its use for the biocontrol of human pathogens. Overall, UV-C water treatments remain an effective pathogen reduction strategy for use in recirculating hydroponics systems, especially when applied early in production. It is possible that future studies could explore more effective biocontrol interventions which could be added in after a UV-C treatment in order to prevent additional pathogens from colonizing the system throughout the rest of the crop growth cycle. A combination of both methods may be able to combine their respective advantages, if a PGPB product with greater biocontrol potential is able to be identified and optimized for use in hydroponic systems.
Keywords: Hydroponics; Food safety; UV; Lettuce; Microgreens; PGPB